1997
DOI: 10.2307/1389452
|View full text |Cite
|
Sign up to set email alerts
|

Family Secrets: Transnational Struggles among Children of Filipino Immigrants

Abstract: In comparative studies of language proficiency and grades, Filipino second generation youth look relatively successful and assimilated, echoing what we know about their parents: post-1965 Filipino immigrants are predominantly middle-class, college-educated, English-speaking professionals who have integrated easily into U.S. society. Based on fieldwork in two California sites, this paper examines some of the issues and problems confronting second generation Filipino youth. “The family” seems to offer an extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
9

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(142 citation statements)
references
References 7 publications
6
127
0
9
Order By: Relevance
“…At the same time, more attention is needed to identifying the factors associated with relatively poorer outcomes among Filipino, other API, and multiethnic API Americans. The discrepancies of problem behaviors between Chinese and Filipino American youth were most extensive, and coupled with several studies that report heightened risk of mental health problems among Filipino Americans (e.g., Wolf, 1997), it seems urgent to conduct more research on Filipino Americans. The population of multiracial and multiethnic youth is increasing dramatically, yet we know little about them .…”
Section: Implications For Research and Interventionmentioning
confidence: 99%
“…At the same time, more attention is needed to identifying the factors associated with relatively poorer outcomes among Filipino, other API, and multiethnic API Americans. The discrepancies of problem behaviors between Chinese and Filipino American youth were most extensive, and coupled with several studies that report heightened risk of mental health problems among Filipino Americans (e.g., Wolf, 1997), it seems urgent to conduct more research on Filipino Americans. The population of multiracial and multiethnic youth is increasing dramatically, yet we know little about them .…”
Section: Implications For Research and Interventionmentioning
confidence: 99%
“…By the same reasoning, children from advantaged immigrant nationalities who attend schools with a large number of similar coethnics may see their academic gains attenuated by the more competitive environment of such schools and the diminished sense that they are, in some sense, ''special'' (41,42). Although tentative at this point, these ideas will serve as guide points for the exploration of a question not analyzed before, namely, how early school ethnic composition bears on the subsequent academic fate of the new second generation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A review of prevalence rates reported in the most important research studies conducted over the past two decades suggests that rapid acculturation does not necessarily lead to conventionally anticipated outcomes (Vega and Rumbaut, 1991). Thus, teenaged children of middle-class Filipino immigrants, the most "Americanized" of contemporary Asian-origin newcomer groups, exhibit higher rates of suicidal ideation and attempts than most other immigrant groups (see Wolf, 1997;Kann et al, 1995;Rumbaut, 1994b).…”
Section: Assimilation and Its Discontentsmentioning
confidence: 99%